Is it Usher syndrome? Collaborative diagnosis and molecular genetics of patients with visual impairment and hearing loss. (3rd March 2020) - Stiff, Heather A.; Sloan-Heggen, Christina M.; Ko, Ashley; Pfeifer, Wanda L.; Kolbe, Diana L.; Nishimura, Carla J.; Frees, Kathy L.; Booth, Kevin T.; Wang, Donghong; Weaver, Amy E.; Azaiez, Hela; Kamholz, John; et al.
ABSTRACT: Background : Usher syndrome is the most common hereditary syndrome combining deafness and blindness. In the 2017 National Child Count of Children and Youth who are Deaf-Blind, Usher syndrome represented 329 of 10, 000 children, but there were also at least 70 other etiologies of deaf-blindness documented. The purpose of this study was to analyze the work-up and ultimate diagnoses of 21 consecutive families who presented to the Genetic Eye-Ear Clinic (GEEC) at the University of Iowa. Our hypothesis was that most families referred to the GEEC would have initial and final diagnoses of Usher syndrome. Materials and Methods : Patients were identified through an IRB approved retrospective chart review of referrals to the GEEC between 2012 and 2019. Details about each patient's history, exam, and clinical and genetic work-up were recorded. Results : From 2012 to 2019, 21 families (25 patients) were referred to the collaborative GEEC. Overall molecular diagnostic rate in this cohort was 14/21 (67%). Evaluation resulted in a change of diagnosis in 11/21 (52%) families. Ultimately, there were eleven unique diagnoses including hereditary, non-hereditary, and independent causes of combined visual impairment and hearing loss. The most common diagnosis was Usher syndrome, which represented 6/21 (29%) families. Conclusions : Providing a correct diagnosis for patients with visual impairment and hearing loss can be challenging for clinicians and their patients, but it can greatly improve clinical care and outcomes. We recommend an algorithm that includes multidisciplinary collaboration, careful clinical evaluation, strategic molecular testing, and consideration of a broad differential diagnosis.